Special issue: “Post-COVID-19 syndrome”: editorial - Scharf, Rüdiger Eberhard (Viruses, 2024)
On 30 January 2020, the World Health Organization declared COVID-19 a Public Health Emergency of International Concern (PHEIC)—the highest WHO warning level [...]